1999
DOI: 10.1046/j.1469-8137.1999.00494.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two arbuscular mycorrhizal fungi in symbiosis with Allium porrum: inflow and flux of phosphate across the symbiotic interface

Abstract: Individual arbuscular mycorrhizal fungi can differ markedly in their ability to improve the phosphate nutrition and growth of host plants. In particular, Scutellospora calospora is relatively ineffective with some hosts and a growth depression is often observed. We have examined the abilities of S. calospora and Glomus sp. ' City Beach ' strain WUM 16, grown in soils which promote extensive mycorrhizal colonization, to transfer phosphate (P) to Allium porrum. Phosphate uptake from the low-P soils (P ! )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…The increased total root length in response to AM inoculation in maize is similar to those reported by Dickson et al (1999), where Allium cepa L. colonized by S. calospora and Glomus sp. 'City Beach' (Glomus Tul.…”
Section: Discussionsupporting
confidence: 86%
“…The increased total root length in response to AM inoculation in maize is similar to those reported by Dickson et al (1999), where Allium cepa L. colonized by S. calospora and Glomus sp. 'City Beach' (Glomus Tul.…”
Section: Discussionsupporting
confidence: 86%
“…Various lines of evidence suggest that most of the phosphate moves into mycorrhizal roots via the fungus (Pearson and Jakobsen, 1993;Liu et al, 1998b;Chiou et al, 2001), and estimates of phosphate flow into hyphae correlate well with the root measurements, providing further support for this theory (Jakobsen et al, 1992). Based on the phosphate inflow measurements and estimations of the area of the arbuscules, it is suggested that phosphate fluxes across the arbuscular interface range between 2 and 29 nmol·m Ϫ2 ·s Ϫ1 and are comparable to transport rates measured in plant and fungal cells in highphosphate environments (Cox and Tinker, 1976;Smith et al, 1994;Smith and Read, 1997;Dickson et al, 1999). The apparent K m for MtPT4 is in the range expected for optimal activity in a relatively high-phosphate environment.…”
Section: Discussionmentioning
confidence: 56%
“…The concentration of phosphate in the periarbuscular space also is unknown, but estimates of the flux across the arbuscule have been made. Phosphate flow into mycorrhizal roots is significantly higher than that into nonmycorrhizal roots, and depending on the phosphate concentration of the external medium, fluxes of between 8 and 100 ϫ 10 Ϫ13 mol·m Ϫ1 (root)·s Ϫ1 have been measured (Cox and Tinker, 1976;Smith et al, 1994;Smith and Read, 1997;Dickson et al, 1999). Various lines of evidence suggest that most of the phosphate moves into mycorrhizal roots via the fungus (Pearson and Jakobsen, 1993;Liu et al, 1998b;Chiou et al, 2001), and estimates of phosphate flow into hyphae correlate well with the root measurements, providing further support for this theory (Jakobsen et al, 1992).…”
Section: Discussionmentioning
confidence: 64%
“…We now know that AMF strains differ dramatically in metabolic strategies such as amount of C extracted from their hosts (Jakobsen et al 1992), amount of lipids allocated to storage (van Aarle & Olsson 2003), the transfer of P to their host plants (Boddington & Dodd 1999), C transport capacities across symbiotic interfaces (Dickson et al 1999), and colonization and hyphal-length allocation (Smith et al 2000, Hart & Reader 2005. Fungal allocation strategies can determine benefits conferred to the host.…”
Section: Lozano 2003) There Is No One Single Attribute (Such As N2 Fmentioning
confidence: 99%